Combination Of VADER Sentiment Analysis and SEQ Scale For Evaluating the Usability of The Gojek Application - Zakiyah Apriliya Budiarti; Tenia Wahyuningrum; Adnan Purwanto; Muhammad Akbar Setiawan; Singgih Setia Andiko; Abdul Karim (Scientific Journal of Informatics, 2026)
Purpose: This study aims to analyze user sentiment toward the Gojek mobile application using the Valence Aware Dictionary for Sentiment Reasoning (VADER) method and to evaluate the perceived ease of use of the application using the Single Ease Question (SEQ) instrument. Methods: The research data were obtained by scraping 30,000 user reviews of the Gojek application from the Google Play Store. The reviews were processed through text preprocessing, sentiment classification using the VADER method, and subsequent mapping of sentiment polarity scores to a 1–7 SEQ usability scale. A Spearman rank correlation analysis was conducted to examine the relationship between sentiment scores and derived SEQ values. Result: The results indicate that user sentiment toward the Gojek application is predominantly positive, followed by neutral and negative sentiments. The overall average SEQ score is 4.11, suggesting that the application is generally perceived as fairly easy to use. Furthermore, a strong and statistically significant positive association was found between VADER sentiment scores and SEQ usability scores, indicating that more positive sentiment tends to be associated with higher perceived ease of use. Novelty: This study contributes to the literature by empirically integrating sentiment analysis and usability evaluation using VADER and SEQ within the context of an Indonesian super-app. The findings provide practical insights for digital application developers to identify usability strengths and areas for improvement based on large-scale user feedback.